The role of public associations in the Implementation of out-of-school education - Tsybanyuk, Oleksandra (My University, 2021)
The main purpose of the study is to analyze the role of public associations in the implementation of out-of-school education. The system of out-of-school education is characterized by the purposeful functioning of teaching, upbringing, development and socialization of the individual in his free time, with its special structures, connections and relationships between elements. Out-of-school education is a systemic object both in its content and in its procedural aspects. The semantic components of out-of-school education are culture, society, nature, people. The procedural components of out-ofschool education include the family, educational institutions, libraries, clubs, children's, student and organizations, societies, and the media. As a result, the role of public associations in the implementation of out-of-school education was determined.
Keywords: Pedagogy. Education. Out-of-school education. Public associations. Training.